DERIVATIONAL SUFFIXES FOUND IN SELECTED ARTICLE IN TEMPO ENGLISH MAGAZINE - Ni Nyoman Ayuk Suandari; I Gusti Bagus Wahyu Nugraha Putra (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2023)
This research aims to find out the type of derivational suffixes and the morphological process of derivational suffixes which found in selected article of law in Tempo English Magazine. Descriptive qualitative and quantitative method were used to identify the type and the morphological process of derivational suffixes. There are 59 data were found in three articles of law in Tempo English Magazine which were: derivational suffixes Noun to Adjective 5 data (8,43%) such as: -ic and –an. Derivational suffixes Verb to Noun 31 data (52,54%) such as: -ance, -ation, -er, -ion. Derivational suffixes Adjective to Adverb 16 data (27,12%) such as: -ly. Derivational suffixes Noun to Verb 2 data (3,39%) wich were: -ize, -ate. Derivational suffixes Adjective to Noun 2 data (3,39%) which were: -ity. And derivational suffixes Verb to Adjective 3 data (5,08%) like: -ity. The data that has the most occurrences is derivational suffixes Verb to Noun, while the data that has the fewest occurrence are derivational suffixes Noun to Verb and Adjective to Noun. Keywords: Derivational suffixes; morphology; Tempo English Magazine